The Relationship of Adolescents’ Self-Attitude and the Choice of Preferred Behavior Style in a Conflict Situation - Zhamkotsyan, Ruzanna (ՀՀ ԳԱԱ)
Adolescence is a difficult period of sexual and psychological maturation. The transition from childhood to adulthood takes place at this stage with all aspects of development: physical, mental, moral, social, as a result of which qualitative new formations are created. The main new formation of this age is the development of self-awareness. The self-awareness demonstrated by a teenager leads to the formation of a relatively stable level of self-esteem and ambition, which creates a request for independence, self-affirmation, and recognition of one’s rights by adults. During adolescence, the formation of self-awareness and self-esteem is greatly influenced by communication with peers. For the process of successful socialization and adaptation of a teenager, a person’s interpersonal relationships play an important role, on which a person’s mental and psychological health and the success of educational activities also depend. During socialization, personal characteristics, consciousness and self-awareness with its components are formed, which, in turn, have a great influence on interpersonal relationships, the emergence and overcoming of interpersonal conflicts. Подростковый возраст – сложный период сексуального и психологического взросления. На этом этапе происходит переход от детства к взрослости со всеми сторонами развития: физическим, психическим, нравственным, социальным, в результате чего формируются новообразования. Главным новообразованием этого возраста является развитие самосознания. Самосознание, проявляемое подростком, приводит к формированию относительно стабильного уровня самооценки и амбиций, что создает потребность в независимости, самоутверждении, признании своих прав со стороны взрослых. В подростковом возрасте на формирование самосознания и самооценки большое влияние оказывает общение со сверстниками. Для процесса успешной социализации и адаптации подростка важную роль играют межличностные отношения человека, от которых также зависит психическое и психологическое здоровье человека, успех учебной деятельности. В ходе социализации формируются личностные характеристики, сознание и самосознание с его компонентами, которые, в свою очередь, оказывают большое влияние на межличностные отношения, возникновение и преодоление межличностных конфликтов. Դեռահասության տարիքը աձնավորության կյանքի սեռական և հոգեբանական հասունացման դժվար շրջանն է: Մանկությունից հասունության անցումը այս փուլում տեղի է ունենում զարգացման բոլոր` ֆիզիկական, մտավոր, բարոյական, սոցիալական կողմերով, որի արդյունքում ձևավովում են որակական նոր կազմավորումներ: Այս տարիքի հիմնական նորագոյացությունը ինքնագիտակցության զարգացումն է: Դեռահասի մոտ դրսևորվող ինքնագիտակցությունը հանգեցնում է հարաբերականորեն կայուն ինքնագնահատականի և հավակնությունների մակարդակի ձևավորմանը, որն էլ ինքնուրույնության, ինքնահաստատման, մեծահասակների կողմից իր իրավունքների ճանաչման պահանջմունք է առաջացնում: Դեռահասի հաջող սոցիալականացման և հարմարման գործընթացի համար կարևոր դեր ունեն անձի միջանձնային հարաբերությունները, որոնցից կախված է նաև անձի հոգեկան ու հոգեբանական առողջությունը, ուսումնական գործունեության հաջողությունը: Սոցիալականացման ընթացքում ձևավորվում են անձնային առանձնահատկությունները, գիտակցությունն ու ինքնագիտակցությունն իր բաղադրիչներով, որոնք իրենց հերթին մեծ ազդցություն ունեն միջանձնային հարաբերությունների ու միջանձնային կոնֆլիկտների առաջացման ու հաղթահարման վրա:
Keywords: Social and Humanitarian Sciences